PENGARUH LINGKUNGAN KELUARGA TERHADAP SUMBER BELAJAR MENULIS TEKS DESKRIPSI - Pajriyanti, Yuni; Indihadi, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a quantitative study of Indonesian language education, especially on the influence of the family environment on learning resources for writing descriptive texts. This study aims to determine the influence of the family environment on learning resources for writing descriptive texts for students at Derah Elementary Schools in Tasikmalaya Regency. The method used in this study is an experimental method with a one group pretest-posttest approach, with a sample of 23 students. The results of the study showed: There is a significant influence of the family environment on learning resources for writing descriptive texts at Derah Elementary Schools in Tasikmalaya Regency. This can be seen from the results of calculations using SPSS which were carried out and analyzed in this study. From the description of the data before the treatment, the pretest scores showed that most students were in the low (60.87%) and medium (39.13%) categories. After being given the first treatment, 34.78% of students were in the high category and 65.22% were in the medium category. Then given the second treatment, the results were 69.56% of students were in the high category, even 4.34% reached the very high category. And finally, a posttest was conducted with a value of 56.52% in the very high category, and 43.48% in the high category.